A bivariate generalized linear exponential distribution: properties and estimation. Issue 9 (27th September 2022) - Pathak, A. K.; Vellaisamy, P.
Abstract: This article introduces a new family of bivariate generalized linear exponential (BGLE) distributions, whose marginals are generalized linear exponential (GLE) distributions. We derive the expressions for regression function, product moments and the stress–strength parameter P ( X < Y ) for the BGLE distribution. Several statistical properties, a local dependence function and some association measures are studied. Further, we discuss the associated copula and its various important properties. Finally, the maximum likelihood estimators for the parameters are obtained and an application to a real data set is also discussed.